Free, soluble conjugated and insoluble bonded phenolic acids in Keemun black tea: From UPLC-QQQ-MS/MS method development to chemical shifts monitoring during processing. (May 2022) - Lai, Guoping; Cui, Yuqing; Granato, Daniel; Wen, Mingchun; Han, Zisheng; Zhang, Liang
Graphical abstract: Highlights: The UPLC-QQQ-MS method for quantitation of phenolic acids was established. The relation between phenolic acids during processing of Keemun black tea were quantified. The adduct of (-)-epigallocatechin gallate and chlorogenic acid was identified. Abstract: Phenolic acids, including benzoic acid and hydroxycinnamic acid derivatives, are the main compounds of black tea. An efficient and accurate analytical method to quantify ten phenolic acids was established and validated by ultra-performance liquid chromatography coupled with triple quadrupole mass spectrometry (UPLC-QQQ-MS/MS). The chemical shifts during the processing of Keemun black tea were analyzed and the phenolic acids were quantified. Compared with fresh tea leaves, after processing, the contents of free phenolic acids, including gallic acid, salicylic acid, p -coumaric acid, and ferulic acid, increased markedly. Still, the contents of soluble conjugated phenolic acids, including p -coumaroylquinic acid isomers and chlorogenic acid isomers, decreased. Furthermore, the total contents of lignin, and insoluble bonded phenolic acids decreased. The adduct of (-)-epigallocatechin gallate and 3-caffeoylquinic acid was detected in tea samples, and its content increased highly after fermentation. The developed and validated analytical method can be used to monitor the manufacturing process of black tea.